Comparison of photodamage in non-pigmented and pigmented human skin equivalents exposed to repeated ultraviolet radiation to investigate the role of melanocytes in skin photoprotection - De Los Santos Gomez, Paola; Costello, Lydia; Goncalves, Kirsty; Przyborski, Stefan (Frontiers in Medicine, 2024)
Introduction: Daily solar ultraviolet (UV) radiation has an important impact on skin health. Understanding the initial events of the UV-induced response is critical to prevent deleterious conditions. However, studies in human volunteers have ethical, technical, and economic implications that make skin equivalents a valuable platform to investigate mechanisms related to UV exposure to the skin. In vitro human skin equivalents can recreate the structure and function of in vivo human skin and represent a valuable tool for academic and industrial applications. Previous studies have utilised non-pigmented full-thickness or pigmented epidermal skin equivalents to investigate skin responses to UV exposure. However, these do not recapitulate the dermal-epidermal crosstalk and the melanocyte role in photoprotection that occurs in vivo. In addition, the UV radiation used in these studies is generally not physiologically representative of real-world UV exposure.Methods: Well-characterised pigmented and non-pigmented skin equivalents that contain human dermal fibroblasts, endogenous secreted extracellular matrix proteins (ECM) and a well-differentiated and stratified epidermis have been developed. These constructs were exposed to UV radiation for x5 consecutive days with a physiologically relevant UV dose and subsequently analysed using appropriate end-points to ascertain photodamage to the skin. Results: We have described that repeated irradiation of full-thickness human skin equivalents in a controlled laboratory environment can recreate UV-associated responses in vitro, mirroring those found in photoexposed native human skin: morphological damage, tanning, alterations in epidermal apoptosis, DNA lesions, proliferation, inflammatory response, and ECM-remodelling.Discussion: We have found a differential response when using the same UV doses in non-pigmented and pigmented full-thickness skin equivalents, emphasising the role of melanocytes in photoprotection.